The effect of unintentional oxygen incorporation into Cr-CrN-DLC coatings deposited by MePIIID method using filtered cathodic vacuum arc carbon and metal plasma - Walkowicz, J.; Bujak, J.; Zavaleyev, V. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
The multilayer Cr-CrN-DLC coatings deposited by MePIIID method on substrates made of high speed steel HS 6-5-2 were studied. The streams of filtered carbon and metal arc plasma were used in both ion implantation and deposition phases. Investigation of the chemical composition of Cr-CrN-DLC coatings revealed considerable amount of oxygen in deposited DLC film. Additional alloying of DLC films with chromium reduced the concentration of oxygen. The presence of oxygen affects the properties of DLC coatings, which was confirmed by the investigation of the hardness and adhesion. Изучаются многослойные покрытия Cr-CrN-DLC, осажденные методом MePIIID, на подложках из быстрорежущей стали HS 6-5-2. Отфильтрованные потоки углеродной и металлической плазмы использовались в ионной имплантации и осаждении покрытий. Исследование химического состава Cr-CrN-DLC-покрытий показало значительное количество кислорода в осажденных DLC-пленках. Дополнительное легирование пленок DLC хромом сократило концентрацию кислорода. Присутствие кислорода влияет на свойства покрытий DLC, которые были подвержены исследованиям на твердость и адгезию. Вивчаються багатошарові покриття Cr-CrN-DLC, осадженні методом MePIIID, на підкладках з швидкорізальної сталі HS 6-5-2. Відфільтровані потоки вуглецевої та металевої плазми використовувались в іонній імплантації та осадженні покриттів. Дослідження хімічного складу Cr-CrN-DLC-покриттів виявило значну кількість кисню в осаджених DLC-плівках. Додаткове легування плівок DLC хромом зменшило концентрацію кисню. Присутність кисню впливає на властивості покриттів DLC, які були досліджені на твердість та адгезію.